Patronage, welfare, tenders, private consultancies, and expert measurement: The example of SDG 4.2 - Penn, Helen (Global social policy, 2017)
This article describes the background to subgoal SDG 4.2. It suggests that as with the SDG process more generally, the goal is a compromise and does not address the critical issue of inequality, The implementation of the goal is dependent on charitable interventions, and likely to be undertaken, if at all, through the processes of tendering with private individuals and companies. Efficacy is measured through globally developed criteria, heavily reliant on USA sources, with little attention to context.